Reflection of national mythology in Chuvash poetry - Nikiforova, Vera Vitalevna (Этническая культура, 2024)
The interaction of myth and literature is an urgent literary problem. Mythological themes, plots, motifs, and images are used and reinterpreted in Chuvash literature throughout its history. The main purpose of this study is to study the peculiarities of the reflection of mythology in Chuvash poetry. The most striking poetic works of Chuvash authors, created within the chronological boundaries of the XX – early XXI century, in the structure of which mythological elements play an important role, served as materials for the study. The main ones are descriptive and systematic methods. For the first time, the article presents an overview analysis of Chuvash poetry of the XX – early XXI century from the point of view of the stated theme. Her study demonstrated that the myth is noticeably reflected in poetic works. They reveal the structural and meaningful elements of myth, as well as signs of mythological thinking and mythological worldview. The conducted research has shown that myth is one of the sources of artistic creativity. In the future, it is supposed to analyze the features of the functioning of myth in prose and drama. The results obtained can be used in the study of the problem of national identity in Chuvash literature.